Societal Entrepreneurship as a Lever to Sustainable Local and Regional Development - the Case of the ALV Theme park - Bengt Johannisson; Elisabeth Sundin (European Regional Science Association (ERSA), 2010)
When the need for development goes beyond economic growth to include also ecological, social and cultural concerns, the means must be broadened beyond financial capital to include also human, social and emotional capital. While human capital concern the intellectual capabilities that people have in term of formal and personal knowledge, social capital refers to the resources that they have access to thanks to their personal networks. Emotional capital is more seldom considered by includes the ability of people to get committed, to engage and passionately get involved in the enactment of own ideas or the protecting the local community from being deconstructed. There are two major strategies to cope with a need for sustainable development - (inter)action or reaction. The last-mentioned creates correctives to the negative consequences of economic focus in present operations. Corporate Social Responsibility (CSR) may be considered as such a corrective. The first-mentioned strategy is an integrated approach to the making of a sustainable organization/locality in a way where economic, social and ecological as well as cultural forces and pressures spontaneously and interactively build a texture out of micro-events which attracts and support further measures. As much as market-oriented research is the obvious point of departure for strategies that guide economic change, social or societal entrepreneurship is an appropriate frame for the proposed integrated approach. The field study concerns Astrid Lindgren's World where the stories told by world-famous Swedish writer of children's books, e.g. Pippi Longstocking are enacted in park in the vicinity of the small town Vimmerby in Southern Sweden. Both the messages communicated by the books/stories and the author's deep involvement in the management of the park reflected a concern for more generic values than the making of a business venture. We will demonstrate that the making of the park into one of Sweden's most attractive destinations for domestic as well as international visitors is the outcome of multiple agency originating in all three sectors..
Keywords: 330